The reciprocal function and regulation of tumor vessels and immune cells offers new therapeutic opportunities in cancer - Missiaen, Rindert (Semin Cancer Biol, 2018)
Tumor angiogenesis and escape of immunosurveillance are two cancer hallmarks that are tightly linked and reciprocally regulated by paracrine signaling cues of cell constituents from both compartments. Formation and remodeling of new blood vessels in tumors is abnormal and facilitates immune evasion. In turn, immune cells in the tumor, specifically in context with an acidic and hypoxic environment, can promote neovascularization. Immunotherapy has emerged as a major therapeutic modality in cancer but is often hampered by the low influx of activated cytotoxic T-cells. On the other hand, anti-angiogenic therapy has been shown to transiently normalize the tumor vasculature and enhance infiltration of T lymphocytes, providing a rationale for a combination of these two therapeutic approaches to sustain and improve therapeutic efficacy in cancer. In this review, we discuss how the tumor vasculature facilitates an immunosuppressive phenotype and vice versa how innate and adaptive immune cells regulate angiogenesis during tumor progression. We further highlight recent results of antiangiogenic immunotherapies in experimental models and the clinic to evaluate the concept that targeting both the tumor vessels and immune cells increases the effectiveness in cancer patients.